2014
DOI: 10.1002/etc.2582
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anionic polyacrylamide products on gill histopathology in juvenile rainbow trout (Oncorhynchus mykiss)

Abstract: Anionic polyacrylamide (PAM) products are commonly used to remove suspended materials from turbid waters and to help mitigate soil erosion. In the present study, juvenile rainbow trout (Oncorhynchus mykiss) were exposed to 3 mg/L to 300 mg/L of 10 commercially available PAM products (Clearflow Water Lynx Polymer Log and Clearflow Soil Lynx Granular Polymer; Clearflow Enviro Systems Group), and gill histological parameters were measured following either 7 d or 30 d of polymer exposure. A cationic polymer produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…14,15 Up to now, a series of anionic polyacrylamide with high occulation performance have been developed and applied in the waste water treatment. 16,17 However, the defect of the APAM, namely, the disordered and random distribution of anionic units in the polymer chain, seriously restricts the further enhancement of the solidwater separation ability. In addition to the molecular weight (MW) and the density of the anionic monomer, the congura-tion and the distribution of anionic units also affect the nal occulation performance.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Up to now, a series of anionic polyacrylamide with high occulation performance have been developed and applied in the waste water treatment. 16,17 However, the defect of the APAM, namely, the disordered and random distribution of anionic units in the polymer chain, seriously restricts the further enhancement of the solidwater separation ability. In addition to the molecular weight (MW) and the density of the anionic monomer, the congura-tion and the distribution of anionic units also affect the nal occulation performance.…”
Section: Introductionmentioning
confidence: 99%
“…Testing of poly(acrylamide) interaction with the gill tissues of several aquatic species including fish [66,73,[75][76][77], crustaceans [66,73,77], algae [66,77] and insects [77] have been carried out. In many studies of adult fish, the anionic and non-ionic form of the poly(acrylamide) cause only low levels of damage to the fish, with effects increasing at higher concentrations [75]. However, sustained exposure of organisms over a 40 day period has shown that low levels of these polymers are intrinsically toxic to almost all aquatic fauna [73].…”
Section: Poly(acrylamides)mentioning
confidence: 99%
“…Even in tests where fish survival was not impacted, the general activity and swimming behaviour of the fish were sub normal [76]. Conversely the cationic form of the polymer is known to be far more toxic, causing pathological issues at sub mg ml −1 concentrations, as the polymer builds up on negatively charged gill surfaces [75,77]. Reduced gill functionality impairs oxygen uptake in the fish and results in death.…”
Section: Poly(acrylamides)mentioning
confidence: 99%
See 1 more Smart Citation
“…The polymers are added to wastewater to improve the settling and the subsequent removal of suspended particles, either by direct flocculation or by neutralising the suspended particles surface charge 18,21 . Both polymers are toxic at very low concentrations to aquatic lifeforms 5 , and whilst it is accepted that the cationic variant of the polymer is substantially more toxic than the anionic polymer both present a risk to the aquatic fauna 22 .…”
Section: Introductionmentioning
confidence: 99%